The status of storks, ibises and spoonbills in Indonesia - Marcel J Silvius; Wim J. M Werhaugt (KUKILA, 1989)
A brief summary is given of the current status in Indonesia of the eleven Stork, Ibis and Spoonbill species occurring in Indonesia. Of these the Storm's Stork, Royal Spoonbill, and White-shouldered Ibis are considered as endangered and likely to disappear in Indonesia within the next decades if no conservation action is undertaken. Ongoing conservation programmes for the species are discussed and additional conservation measures outlined.